STUDI DRAINASE PADA PERSIMPANGAN JALAN KADRI OENING DAN JALAN PANGERAN SURYANATA KOTA SAMARINDA - Ardian, Yuli Arianto (KURVA S JURNAL MAHASISWA, 2014)
Disposal of excess water which is not desirable in an area of intersection as the Road Kadrie Oening and Princes Street Suryanata and ways alleviation consequences caused by excess water is then made drainage channel as one of the elements of the public infrastructure needed by the people around the site in order towards city life that is safe, comfortable, clean, healthy and free of flooding. Drainage infrastructure here serves to drain surface water from the road as the surface water control measures to improve the area around the location of the intersection of muddy puddles and flooding                    The intent of this study was to determine the drainage system in the area - area of intersection Kadrie Suryanata Oening and Prince Street in the city of Samarinda.                    Rainfall intensity side channel at the intersection of Princes Street Kadri Oening and Suryanata in Samarinda, with a return period of 2, 5, 10 and 25 years using the Log Pearson III as follows;LokasiDebit Rancangan (Q) m3/dtk Periode Ulang 2 TahunPeriode Ulang 5 TahunPeriode Ulang 10 TahunPeriode Ulang 25 Tahun    Lokasi 10,31350,52780,66630,8609  Lokasi 20,10310,17360,21920,2832  Lokasi 30,47440,79861,00821,3026  Lokasi 40,10420,17540,22140,2861  Lokasi 50,09940,16720,21110,2728  Lokasi 60,11200,18850,23790,3074  Lokasi 70,51080,85991,0851,4025  Lokasi 80,13720,23090,29150,3766  Lokasi 90,37070,62400,78771,0177  Lokasi 100,40150,67580,85311,1023  Lokasi 110,24920,41940,52950,7095  Lokasi 120,26320,44300,55930,7226  Lokasi 130,12710,21400,27400,3490  Lokasi 140,49010,82501,04141,3456  Lokasi 150,30270,50950,64320,8311  Lokasi 160,24920,41940,52950,6841  Debit ( Q ) The channel is 1.4025 m3 / sec . Dimensional cross section of the channel drainage systems on waterways divided ;a.             Channel side ( lengthwise ) on the left and right side in Jalan Kadri Oening and Princes Street Suryanata should be improved by changing the dimensions of the channel and to be easy in the implementation of the field then the channel is made uniform with concrete material taken 1.5 m size B and H are taken 1 , 2 m , the planning of drainage channels made under the pavement then cover with pavement facilities .b.             Transverse cross-section of the water channel (culvert) or rectangular made of stone masonry and cover plate of concrete, with a cross-sectional dimension; Height (h) = 1,5 meters, width (b) = 1,5 meters. The cover plate of the concrete culvert with size; Thick plates = 20 cm; Principal reinforcement Ø = 12, a distance of 200 cm (D12 – 200); Dividers diameter reinforcement Ø = 8, a distance of 250 cm (D8 – 250).